2020
DOI: 10.1186/s12957-020-01956-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hyperthermic intraperitoneal chemotherapy (HIPEC) in the management of malignant ascites

Abstract: Objective: The purpose of this study is to compare the difference of clinical efficacy between conventional intraperitoneal chemotherapy and HIPEC, so as to explore the clinical application value and advantages of HIPEC. Design: A retrospective analysis was conducted on 80 patients with malignant ascites admitted to our hospital from June 2017 to June 2019. The general clinical data and qualitative data of the treatment results of 80 patients with malignant ascites were processed by SPSS19.0 using χ 2 test, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The results suggested that HIPEC had a significant advantage in controlling malignant ascites in those patients. A study showed that HIPEC combined with systemic chemotherapy also achieve ascites control, with few adverse events [ 40 ]. In addition, except for two side effects associated with oxaliplatin, i.e., neutropenia and neurotoxicity, HIPEC did not significantly increase the incidence of adverse events within 30 days after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that HIPEC had a significant advantage in controlling malignant ascites in those patients. A study showed that HIPEC combined with systemic chemotherapy also achieve ascites control, with few adverse events [ 40 ]. In addition, except for two side effects associated with oxaliplatin, i.e., neutropenia and neurotoxicity, HIPEC did not significantly increase the incidence of adverse events within 30 days after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…First the infusion uid can mechanically remove abdominal isolated cancer cells. Then during the process, chemotherapeutic drugs are infused into the abdominal cavity, so as to form a circumstance of high and durable concentration in the peritoneal cavity [12]. There is a natural peritonealplasma barrier (PPB) in our body,which limits the resorption of drugs from the peritoneal cavity into the blood [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although no randomized trials exist to study the use of LS-HIPEC in the treatment of malignant ascites, it has been favorably reported in several series, offering an option to palliate this difficult problem [ 20 , 21 , 22 ]. These studies demonstrate that a significant reduction in ascites can be achieved in 91–94% of patients in reported series [ 22 , 23 ]. While rates of significant complications (Grade 3 or 4) are low, even in these medically frail patients, ranging from 2 to 12% [ 22 , 24 ].…”
mentioning
confidence: 80%